2015
DOI: 10.1002/2014gl062521
|View full text |Cite
|
Sign up to set email alerts
|

Seismic observation of an extremely magmatic accretion at the ultraslow spreading Southwest Indian Ridge

Abstract: The oceanic crust is formed by a combination of magmatic and tectonic processes at mid-ocean spreading centers. Under ultraslow spreading environment, however, observations of thin crust and mantle-derived peridotites on the seafloor suggest that a large portion of crust is formed mainly by tectonic processes, with little or absence of magmatism. Using three-dimensional seismic tomography at an ultraslow spreading Southwest Indian Ridge segment containing a central volcano at 50°28′E, here we report the presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
58
0
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 62 publications
(65 citation statements)
references
References 40 publications
6
58
0
1
Order By: Relevance
“…Morgan and Ghen, 1993;Canales et al, 1998;Li et al, 2015). Morgan and Ghen, 1993;Canales et al, 1998;Li et al, 2015).…”
Section: Variations In the Magma Supply In The Swsbunclassified
“…Morgan and Ghen, 1993;Canales et al, 1998;Li et al, 2015). Morgan and Ghen, 1993;Canales et al, 1998;Li et al, 2015).…”
Section: Variations In the Magma Supply In The Swsbunclassified
“…(a) Bathymetry map of the central Southwest Indian Ridge (SWIR), fracture zones (FZ), and off‐axis high‐topography edifices modified from Li et al . []. Black dots represent sample locations in this study.…”
Section: Introductionmentioning
confidence: 99%
“…There is a bathymetric high and a mantle Bouguer anomaly (MBA) low between the Indomed (IFZ) and Gallieni (GFZ) fracture zones (46°E and 52°20′E, Figure a) [ Georgen et al ., ]. At 50°28′E with the shallowest water depth and the only axial high along this region (Figure b), seismic studies indicate the thickest oceanic crust along ultraslow‐spreading ridges [ Carbotte et al ., ] up to 10 km thick [ Niu et al ., ] and off axis [ Li et al ., ], suggesting that robust magmatism at this particular location has lasted at least 3 Ma [ Li et al ., ]. Off‐axis topographic and gravimetric studies further extend such a melting anomaly to persist for 10 Ma [ Sauter et al ., ].…”
Section: Introductionmentioning
confidence: 99%
“…A unique segment centered at 50°28 0 E shows obviously low magnetic anomaly at its center. Li et al (2015) used three-dimensional seismic tomography at 50°28 0 E and revealed a low-velocity anomaly (*0.6 km/s) which was accompanied by an unusually thick crust (*9.5 km). Niu et al (2015) also identified the thick crust (*10 km) beneath the segment center by wide-angle seismic reflection.…”
Section: Introductionmentioning
confidence: 99%